Improving Water Use and Sugarcane Yield Using Irrigation Strategies in Nicaragua - Rafael Menezes Pereira; Felipe Schwerz; Adriano Valentim Diotto; Carolina Altamirano Oñate; Marlon Daniel Vargas Sandoval; Braulio Otomar Caron; Bernardo Cândido (AgriEngineering)
One of the greatest challenges in crop science worldwide is balancing crop production and water management. In the context of sustainability and vertical production growth, understanding water relations is fundamental for improving crop management in irrigated and rainfed sugarcane fields. Adequate irrigation management can improve water use efficiency and agronomic performance. Nicaragua, due to its limited research and information on irrigation, has significant opportunities to increase crop yields and enhance water efficiency. Therefore, the aim of this study was to evaluate the response of sugarcane growth, yield, and water use efficiency under different irrigation management strategies. The study was performed in a field area from Casur Sugarcane mill in Nicaragua during the crop cycle 2021/2022. The experimental area was cultivated in high clay soil, with the variety CP72-2086 in the second cut with the furrow irrigation method. Two treatments were evaluated, irrigation based on soil moisture (ISw) and irrigation with fixed intervals (IFI), and their effect on growth variables and crop yield. On a temporal analysis, the plants showed compensatory growth in IFI, recovering from water-deficit stress in most measured variables. Sugarcane yield was statistically different between the treatments with 97.87 and 83.84 Mg ha−1 for ISw and IFI, respectively. The water use efficiency was similar for both irrigation strategies. Based on the results found by the authors, it is recommendable to manage irrigation based on soil moisture content because of the best growth response and sugarcane yield.